Use of kaolin as a summer stress alleviating product in olive orchards under rainfed conditions - Brito, Cátia (2019)
In a changing world, where is expected the temperatures rising and the reduction in precipitation in some semi-arid areas of the globe, the search for new agronomic practices that help crops to maintain and/or increase yields and quality is a continuous challenge. Kaolin (KL) exogenous application has been considered a short-term solution to alleviate the adverse effects of summer stress. The formed particle film increases the reflection of excess radiation reducing the risk of leaf damage from heat load accumulation and solar injury. Olive trees (Olea europaea L.) cultivated under rainfed conditions were sprayed with KL (5%) during two consecutive years in the beginning of the summer season. In general, relatively to the control group, KL-sprayed plants showed an enhancement in leaf water status, stomatal conductance and photosynthetic capacity and a reduction in leaf sclerophylly. In the severest period analyzed, at the end of the second-year summer, KL has lost the effectiveness of keeping gas exchange above the control measurements. However, in both years, allowed a faster restauration of the physiological functions in early autumn and contributed to higher crop yield. Overall, the results of the present investigation revealed that KL were effective in preventing the adverse effects of summer stress on crop performance and yield.